Seed germination in sedges: a short review - Żukowski, Waldemar; Bogdanowicz, Agnieszka; Lembicz, Marlena (Biodiversity: Research and Conservation, 2011)
Five patterns of seed germination in the sedges of the genus Carex are presented, based on the literature data and the results of the authors' own research. They include the pattern of C. acutiformis, C. arenaria, C. remota, C. flava and C. communis. These patterns were constructed on the basis of seed specific requirements for development, such as stratification, temperature, dormancy and time of germination. Majority of sedges follow the pattern of C. acutiformis or C. remota. In both cases, stratification and either high or low temperature are essential for seed germination. Seeds that start to germinate early (C. remota pattern) are characterized by the absence of the distinct peaks of germination, as opposed to the C. acutiformis pattern with the germination peak in March. Our long-term investigations, conducted on the group of individuals in controlled conditions, revealed significant differences in seed size and the ability of seeds to germinate depending on the age of mother plants. We postulate that mother plant age is a new factor that should be considered in the construction of seed germination patterns.